Depth distribution of organic carbon sources in Arctic Chukchi Sea sediments. (May 2022) - Zinkann, Ann-Christine; Wooller, Matthew J.; Leigh, Mary Beth; Danielson, Seth; Gibson, Georgina; Iken, Katrin
Abstract: Climate-induced changes in the composition of organic matter sources in Chukchi Sea sediments could have major implications on carbon cycling, carbon sequestration, and food sources for lower benthic trophic levels. The aim of this study was two-fold: (1) to identify the proportional contributions of organic matter from various primary producers (phytoplankton, terrestrial, and bacterial) to depth-stratified sediments (0–5 cm) across the Arctic Chukchi Sea shelf using essential amino acid (EAA) specific stable carbon isotope biomarkers; and (2) to experimentally evaluate sediment bacterial production under different temperature scenarios. Proportional contributions of EAA sources to surface sediments had little relationship with environmental variables across the Chukchi Shelf and only showed noticeably higher terrestrial proportions in surface sediments in a high-deposition region in the southern study area. Across all sediment depth strata, the majority of EAA in sediments (∼76%) originated from terrestrial sources and may be indicative of accumulation over time due to slow degradation processes of this source within sediments. The different EAA sources showed no significant differences in proportional contributions with sediment depth except for phytoplankton-derived EAA, which decreased with increasing sediment depth. These patterns indicate a well-mixed upper sediment horizon, possibly from bioturbation activities by the abundant benthos. One EAA source assumed to respond quickly to changing environmental conditions are bacteria. To evaluate if and how bacterial production would respond to elevated temperatures, sediment bacterial production was measured experimentally using phospholipid fatty acid (PLFA) analysis. Bacterial production was initially (first 24 h) higher at 5 °C than at 0 °C; however, a drawdown of substrate or potential increase in predation activity and viral lysis resulted in bacterial production to subsequently be similar at both temperature settings. Overall results of this study suggest that terrestrial and bacterial carbon sources may become more prominent in a future, warmer Arctic. Identifying current patterns and potential shifts in organic matter sources with changes in temperature can aid in the understanding of the consequences of climate change in terms of organic matter presence and flow through benthic consumers that use these shelf sediments as feeding grounds.